Classic psychedelics, health behavior, and physical health. (November 2022) - Simonsson, Otto; Hendricks, Peter S.; Chambers, Richard; Osika, Walter; Goldberg, Simon B.
Background: Preliminary evidence suggests that classic psychedelics may be effective in the treatment of some psychiatric disorders, yet little remains known about their effects on health behavior and physical health. Objectives: The purpose of this study was to investigate associations of lifetime classic psychedelic use and psychological insight during one's most insightful classic psychedelic experience with health behavior and physical health. Methods: Using data representative of the US population with regard to sex, age, and ethnicity ( N = 2822), this study examined associations of lifetime classic psychedelic use and psychological insight with health behavior and physical health. Results: Lifetime classic psychedelic use was associated with more healthy tobacco-related and diet-related behavior ( β = 0.05 and 0.09, respectively). Among lifetime classic psychedelic users ( n = 613), greater Psychological Insight Questionnaire (PIQ) total scale, PIQ Avoidance and Maladaptive Patterns (AMP) subscale, and PIQ Goals and Adaptive Patterns (GAP) subscale scores were each associated with higher odds of more healthy exercise-related behavior [adjusted odds ratios (aOR) (95% confidence interval, CI = 1.38 (1.13–1.68), 1.38 (1.13–1.68), and 1.32 (1.10–1.60), respectively] and higher odds of having a healthy body mass index (BMI) [aOR (95% CI) = 1.32 (1.07–1.63), 1.36 (1.10–1.69), and 1.23 (1.01–1.50), respectively], and greater GAP subscale scores were associated with more healthy diet-related behavior ( β = 0.10). All PIQ scales were positively associated with some health behavior improvements (overall, diet, exercise) attributed to respondents' most insightful classic psychedelic experience ( β = 0.42, 0.18, and 0.17; β = 0.40, 0.19, and 0.17; and β = 0.40, 0.15, and 0.15, respectively), but only PIQ total scale and AMP subscale scores were positively associated with alcohol-related health behavior improvements ( β = 0.13 and 0.16, respectively). Conclusion: Although these results cannot demonstrate causality, they suggest that psychological insight during a classic psychedelic experience may lead to positive health behavior change and better physical health in some domains, in particular in those related to weight management.